Hukum dan Kekuasaan Sebagai Satu Mata Uang dengan Dua Sisi - Manab, Abdul (WELFARE STATE Jurnal Hukum, 2024)
Law and power have a very close relationship, that relationship can be described as one coin with two sides. The symbolic relationship between law and power is a functional relationship between the two. Power has a function as a tool for forming laws, enforcing laws and implementing laws, while the legal function of power includes tools for legalizing or justifying power, tools for regulating and controlling power and also tools for monitoring and accommodating power accountability. At a theoretical level, the influence of law and power is a reciprocal influence that controls and complements each other. Because power without law will have a strong potential for arbitrariness, while law without power will have no coercive power in implementing and realizing security, order and regularity in the life of society, nation and state, in other words, if there is conflict, the energy of law is often defeated. strong with power energy. As a result, the legal model is very dependent on the type of power. An authoritarian power will give birth to laws that are conservative and orthodox. On the other hand, democratic power will give birth to laws that are responsive and populist.